(untitled) (TAMADDUN NURI JURNALI, 2024)
This article will focus on further improvement of the activities of Information Services reflected in the decisions of the president of the Republic of Uzbekistan, the high appeal of our society to the media and mediamarkases to be viewed as confidence in the celebration of Democratic demands. At the same time, serious, innovative changes in the democratization and modernization of the national press should be carried out and, above all, the need for innovative thinking, press personnel prone to new thinking and research, specialists is indicated.